Improvement and optimization of the classical gastric biopsy culture technique forHelicobacter pyloridiagnosis using trypsin. Issue 6 (June 2015) - Peretz, Avi; Paritsky, Maya; Pastukh, Nina; Koifman, Anna; Brodsky, Diana; Glyatman, Tatyana; On, Avi
Abstract : N/A: Helicobacter pylori infection represents a key factor in the aetiology of various gastrointestinal diseases. H. pylori infection diagnosis is generally achieved using both invasive (e.g. biopsy of the gastric epithelium) and non‐invasive methods. Therefore, cultivation on a growth medium becomes complex. Trypsin is a proteinase enzyme that plays a role in an early stage of tissue digestion. In this study, we used trypsin in order to improve the diagnostic sensitivity of the H. pylori cultivation technique. We used 46 duplicate antrum biopsy specimens, divided into trypsin‐treated and non‐treated groups. The tissues were seeded on a selective H. pylori growth agar medium. We demonstrated that the classic H. pylori culture technique misses the growth of a large number of H. pylori colonies. Significantly more colonies were found in the trypsin‐treated specimens group.